Analysis of Politeness Strategies Contained in The Denny Sumargo Instagram’s Comments (Conference on English Language Teaching, 2023)
Anggaraini, S & A. Damanhuri.2017. Language Feature of Wmen‟s Responses toward Justin Bieber‟s Instagram Post. Language Horizon, 1 (1): 50-57Brown, P., dan Levinson, S. (1987). Politeness Some Universals in Language Usage. Cambridge University Press.Choyimah, Nurul. 2015. Utterances and their Meanings. Tulungagung: IAIN Tulungagung Press.Griffin, E. (2012). A First Look At Communication Theory: eight edition. New York:     McGraw-Hill.Harwood,  C.  2017. “Politeness  and  University  Student  Online  Communication”.        Journal  of the Faculty of Foreign Studies, 35-45.        https://doi.org/https://doi.org/10.34050/els- jish.v1i1.4043Kamsali, I. (2017). The Positive Politeness in Conversation performed by The      Students of English Study Program of Timor University. Journal of Physical           Chemistry B, 8(1), 28– 48. https://doi.org/https://doi.org/10.1016/S0009- 2614(00)00764-8Kusno, A. (2015). Pematuhan dan Pelanggaran Prinsip Kesopanan Serta Fungsinya dalam           Wacana Terkait Usulan Dana Aspirasi DPR di Rubrik Politik Kompasiana. Widyaparwa, 43(1), 65–78. https://doi.org/https://doi.org/10.26499/               wdprw.v43i1.106Kusno, A., & Rahman, A. (2016). BentukBentuk Pelanggaran Prinsip Kesopanan dalam       Ceramah Keagamaan. LiNGUA: Jurnal Ilmu Bahasa Dan Sastra, 11(2), 103–115.               https://doi.org/10.18860/ling.v11i2.350Lakoff, R. (1972). Language in Context. Linguistic Society of America.Mansoor, I. K. (2018). Politeness: Linguistic Study. International Journal of Research in                                                                  Social Sciences and Humanities. 8(4), 167-179 NorraMaros,  M.  &  L. Rosli.2017. “Politeness  Strategies  in  Twitter  Updates  of  Female  Language Studies   Malaysian   Undergraduates”. The   Southeast   Asian   Journal              of   English Language Studies,23(1): 132-14Mukhtar. (2013). Metode Praktis Penelitian Deskriptif Kualitatif. Referensi (GP Press      Group).Shanthi & Karappan. 2016. Communicative Patterns and Politeness Strategies in „SMS      Your    Views‟  Column  in  A  Local  English  Daily.  Dissertation.  Kuala  Lumpur:             Master  of English As Second Language ProgramSpencer-Oatey, H. (2000). Culturally Speaking: Culture, Communication, and Human              Behavior JournalSugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Alfabeta, CV.                       https://massugiyantojambi.wordpress.com/2011/04/15/teori-motivasi/Tamrin. (2014). Kesantunan Berbahasa Bugis pada Masyarakat Bugis di Kabupaten   Sinjai Provinsi Sulawesi Selatan. Multilingual, 13(2), 208–218.Wardhaugh, R. (2006). An Introduction to Sociolinguistics FIFTH EDITION. Blackwell            Publishing.Widhiarso, W. (2005). Pengaruh Bahasa Terhadap Pikiran: Kajian Hipotesis Benyamin Whorf dan Edward Sapir. Bahasa dan PikiranYetty. (2018). Politeness Strategy on Social Interaction Used by Munanese. ELS Journal     on  Interdisciplinary Studies in Humanities, 1(1),                                    59.Yule, G. (2014). Pragmatik. Pustaka Pelajar